Cell-Produced α-Synuclein Is Secreted in a Calcium-Dependent Manner by Exosomes and Impacts Neuronal Survival - Emmanouilidou, Evangelia (Society for Neuroscience, 2010)
α-Synuclein is central in Parkinson's disease pathogenesis. Although initially α-synuclein was considered a purely intracellular protein, recent data suggest that it can be detected in the plasma and CSF of humans and in the culture media of neuronal cells. To address a role of secreted α-synuclein in neuronal homeostasis, we have generated wild-type α-synuclein and β-galactosidase inducible SH-SY5Y cells. Soluble oligomeric and monomeric species of α-synuclein are readily detected in the conditioned media (CM) of these cells at concentrations similar to those observed in human CSF. We have found that, in this model, α-synuclein is secreted by externalized vesicles in a calcium-dependent manner. Electron microscopy and liquid chromatography–mass spectrometry proteomic analysis demonstrate that these vesicles have the characteristic hallmarks of exosomes, secreted intraluminar vesicles of multivesicular bodies. Application of CM containing secreted α-synuclein causes cell death of recipient neuronal cells, which can be reversed after α-synuclein immunodepletion from the CM. High- and low-molecular-weight α-synuclein species, isolated from this CM, significantly decrease cell viability. Importantly, treatment of the CM with oligomer-interfering compounds before application rescues the recipient neuronal cells from the observed toxicity. Our results show for the first time that cell-produced α-synuclein is secreted via an exosomal, calcium-dependent mechanism and suggest that α-synuclein secretion serves to amplify and propagate Parkinson's disease-related pathology.